2018
DOI: 10.1111/pan.13401
|View full text |Cite
|
Sign up to set email alerts
|

Association between sugammadex and anaphylaxis in pediatric patients: A nested case‐control study using a national inpatient database

Abstract: The present study showed no significant association between sugammadex and perioperative anaphylaxis in pediatric patients who underwent general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Despite the potential utility of sugammadex in this clinical scenario, its use should be considered carefully, and the risk–benefit ratio determined. Sugammadex itself can cause allergic reactions, the incidence of which is only now being recognized and investigated 34,35 . Sugammadex binds aminosteroid molecules, and there is the potential for sugammadex to bind other steroid molecules including hydrocortisone which may have undesirable physiologic effects, especially in the setting of an allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the potential utility of sugammadex in this clinical scenario, its use should be considered carefully, and the risk–benefit ratio determined. Sugammadex itself can cause allergic reactions, the incidence of which is only now being recognized and investigated 34,35 . Sugammadex binds aminosteroid molecules, and there is the potential for sugammadex to bind other steroid molecules including hydrocortisone which may have undesirable physiologic effects, especially in the setting of an allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Sugammadex itself can cause allergic reactions, the incidence of which is only now being recognized and investigated. 34,35 Sugammadex binds aminosteroid molecules, and there intravenous fluids, bronchodilators, corticosteroids, and antihistamines. 5,6,36,37 A systematic approach is necessary for the diagnosis of an intraoperative allergic reaction, confirmation of the offending agent, its management under anesthesia, and the process for appropriate postoperative laboratory and skin testing to guide future anesthetic care.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring period for anaphylaxis extended from the day of rasburicase re-administration to 3 days after exposure when biphasic anaphylaxis was reported [ 8 ]. Anaphylaxis was defined as being assigned the ICD-10 codes for anaphylaxis, either T782 (unspecified anaphylactic shock) or T886 (anaphylactic shock as a side effect of an appropriate drug or a drug properly administered), and being prescribed adrenaline injections during this period [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, other investigators have suggested a lower incidence and perhaps one no greater than placebo or neostigmine. 90,91 Future trials are indicated to more clearly define the incidence of allergic reactions including true anaphylaxis with sugammadex. Regardless of its incidence, as with any medication administered perioperatively or to critically ill patients, ongoing patient monitoring is mandatory to allow for prompt recognition and treat of these issues.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%